Enhancing Retinal Resilience: The Neuroprotective Promise of BDNF in Diabetic Retinopathy - Daniela Maria Tanase; Emilia Valasciuc; Evelina Maria Gosav; Mariana Floria; Oana Nicoleta Buliga-Finis; Anca Ouatu; Andrei Ionut Cucu; Tina Botoc; Claudia Florida Costea (Life)
Diabetic retinopathy (DR), a leading cause of vision impairment worldwide, is characterized by progressive damage to the retina due to prolonged hyperglycemia. Despite advances in treatment, current interventions largely target late-stage vascular complications, leaving underlying neurodegenerative processes insufficiently addressed. This article explores the crucial role in neuronal survival, axonal growth, and synaptic plasticity and the neuroprotective potential of Brain-Derived Neurotrophic Factor (BDNF) as a therapeutic strategy for enhancing retinal resilience in DR. Furthermore, it discusses innovative delivery methods for BDNF, such as gene therapy and nanocarriers, which may overcome the challenges of achieving sustained and targeted therapeutic levels in the retina, focusing on early intervention to preserve retinal function and prevent vision loss.